Dissection of the auxin response pathway using functional and chemical genetic approaches - Larrieu, Antoine Paul (2011)
Notably, the hormone regulates the formation and emergence of lateral roots (LRs). In Arabidopsis thaliana the initiation of lateral root primordia (LRP) is induced by auxin and takes place deep within the parental root. Also, the emergence of the LRP through the overlying tissues is regulated by auxin. It has been shown that the gene LAX3 is expressed in cortical and epidermal directly overlying a LRP. External auxin induces LAX3's expression in all cortical and epidermal cells suggesting that it actsas the activating signal. There are two objectives in this study: the first one is to understand how the expression of LAX3 is regulated and the second one is to identify and characterise novel inhibitors of the induction of LAX3. It has been shown that mutations in ARF7 and ARF19 or IAA14/SLR are sufficient to block LAX3 auxin induction. Using classical genetics approaches, it is shown that ARF7 and ARF19 actually regulate LAX3 positively and negatively, respectively. Furthermore, a canonical Auxin Response Element present in the promoter of LAX3 is shown to negatively regulate its expression. Using transcriptomics datasets, a regulatory network is proposed and several putative candidates have been selected. In order to obtain alternative approaches to dissect the induction of LAX3, a suite of 13 inhibitors (representing 8 distinct classes of compounds) have identified. The major and most promising class has been investigated and shown to interfere most probably with the E2 conjugating enzymes. A model and preliminary results with some of the other inhibitors identified are proposed.